THE CONCEPTUALISATION OF HALAL CERTIFICATION ADOPTION MODEL AMONG SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) IN MALAYSIA - Ismalaili Ismail; Nik Azlina Nik Abdullah; Ima Ilyani Ibrahim; Nurul Farihin Mhd Nasir; Ahmad Nizan Mat Noor; Nik Ab Halim Nik Abdullah, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2023)
This is a conceptual paper for a future study based on the review of the literature related to Halal certification adoption and the role of ResourceBased View (RBV) theory. Despite the Halal industry showing potential for a strong market both locally and globally, the number of Halal-certified Small and Medium-Sized Enterprises (SMEs) remains relatively low. This is partly due to challenges in meeting certification requirements, which are seen as complex and costly, as well as a lack of awareness and concern. Additionally, the Ministry of International Trade and Industry (MITI) has identified various challenges faced by Malaysian manufacturers, including a lack of competitiveness in areas such as processing technology, research and development, distribution networks, product quality, and branding. To address these issues, this study aims to investigate the reasons behind SME owners' reluctance to adopt Halal certification for their food products, and to develop an enhancement model and measurement instrument based on the Resource-Based View (RBV) theory. The paper went on to analyse the issues, concepts and objectives for the forthcoming study through several literatures of various disciplines. The conceptual paper signifies to supplement literatures for academics as reference for their research. The result of this future research may provide information to SMEs on factors and the significance of Halal certification adoption to enhance SMEs’ performance. It will also be relevant to policy-makers who design support mechanisms and schemes to promote the creation and growth of small firms.